Pandemic Disease in the Medieval World Rethinking the Black Death - Green, Monica H.; Symes, Carol (The Medieval Globe Books, 2015)
This ground-breaking book brings together scholars from the humanities and social and physical sciences to address the question of how recent work in the genetics, zoology, and epidemiology of plague's causative organism (Yersinia pestis) can allow a rethinking of the Black Death pandemic and its larger historical significance.